Visual Fictions and the U.S. Treasury Courtesans: Images of 19th-Century Female Clerks in the Illustrated Press - Midori V. Green (Belphégor)
During the Civil War, the United States Treasury began hiring female clerks to work within its departments, a decision that would lead to the federal government becoming, according to historian Cindy Sondik Aron, “the first large, sexually integrated, white-collar bureaucracy in America.” By 1864, a congressional committee had already begun looking into accusations that some of the women were mistresses of government officials and that the Treasury Department had been turned into a harem. A second scandal, this time playing out in the press in 1869, renewed the old imagery of the harem. This article looks at how female Treasury clerks were portrayed in the two most popular illustrated weeklies at the time, Frank Leslie’s Illustrated Newspaper and Harper’s Weekly, as well as The Days’ Doings and Harper’s Bazar, and the use of misleading visual tropes that called women’s characters into question. The employment of these pernicious “visual fictions” aided in the creation of stereotypes of working women that continued well into the twentieth century, which, in turn, contributed to the devaluation of white-collar women and their work.